2021
DOI: 10.1093/mnras/stab2277
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation fraction of local volume galaxies

Abstract: Nuclear star clusters (NSCs) are a common phenomenon in galaxy centres and are found in a vast majority of galaxies of intermediate stellar mass ≈109M⊙. Recent investigations suggest that they are rarely found in the least and most massive galaxies and that the nucleation fraction increases in dense environments. It is unclear whether this trend holds true for field galaxies due to the limited data currently available. Here we present our results on the nucleation fraction for 601 galaxies in the Local Volume … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 161 publications
3
20
0
Order By: Relevance
“…Recently, Poulain et al (2021) studied the nucleation of nearby dwarfs (10 Mpc< d <45 Mpc, and 10 5.5 M ⊙ < M * ,galaxy < 10 9 M ⊙ ; see Habas et al 2020) in low-to-moderate-density environments and found a global nucleation fraction of ∼ 0.23 (including both early-and late-types). The Local Volume (d ≲ 12 Mpc) sample of galaxies (10 2.5 M ⊙ < M * ,galaxy < 10 11.5 M ⊙ ) studied in Hoyer et al (2021) has a global nucleation fraction of ∼ 0.24. Similarly, the analysis of Carlsten et al (2022) of Local Volume dwarfs (10 5.5 M ⊙ < M * ,galaxy < 10 8.5 M ⊙ ) determined a global nucleation fraction of 0.23.…”
Section: Nucleation Fractionmentioning
confidence: 99%
“…Recently, Poulain et al (2021) studied the nucleation of nearby dwarfs (10 Mpc< d <45 Mpc, and 10 5.5 M ⊙ < M * ,galaxy < 10 9 M ⊙ ; see Habas et al 2020) in low-to-moderate-density environments and found a global nucleation fraction of ∼ 0.23 (including both early-and late-types). The Local Volume (d ≲ 12 Mpc) sample of galaxies (10 2.5 M ⊙ < M * ,galaxy < 10 11.5 M ⊙ ) studied in Hoyer et al (2021) has a global nucleation fraction of ∼ 0.24. Similarly, the analysis of Carlsten et al (2022) of Local Volume dwarfs (10 5.5 M ⊙ < M * ,galaxy < 10 8.5 M ⊙ ) determined a global nucleation fraction of 0.23.…”
Section: Nucleation Fractionmentioning
confidence: 99%
“…This result has been interpreted as suggestive that the formation of NSCs in these dwarf galaxies are dominated by the in-spiral and merger of GCs (although NSCs could also grow through in-situ star formation after forming). For galaxies with stellar mass ∼ 10 7 𝑀 , the nucleation fraction is 0.3 − 0.4 in Virgo and Coma cluster, and ∼ 0.2 in the Local Volume (Sánchez-Janssen et al 2019;Hoyer et al 2021;Carlsten et al 2021).…”
Section: Future Distribution Of Gcsmentioning
confidence: 98%
“…The possible connection between GCs and NSCs has been a topic of active research (Sánchez-Janssen et al 2019;Hoyer et al 2021;Carlsten et al 2021). It was found that the nucleation fraction (i.e.…”
Section: Future Distribution Of Gcsmentioning
confidence: 99%
“…The binned galaxy nucleation fraction, NSC masses and stellar masses for galaxies in the Coma, Virgo, Fornax clusters, as well as the MW, M31 and M81, are taken from the compilation of RSJ19 and references therein. During the proofs stage of this manuscript, several other compilations of Local Volume nucleation fraction data were published in the studies of Carlsten et al (2021);Hoyer et al (2021); Zanatta et al (2021); Poulain et al (2021), to which we refer interested readers.…”
Section: Datamentioning
confidence: 99%